2007
DOI: 10.1002/j.2161-1920.2007.tb00032.x
|View full text |Cite
|
Sign up to set email alerts
|

current and future value of human capital: predictors of reemployment compensation following a job loss

Abstract: The authors examined the relationship between an individual's human capital profile-knowledge, skills, abilities, and other characteristics-and compensation before and after a job loss. The results of this study show that the types of human capital that predicted pre-job-loss salary differ from the types that predict reemployment salary. The findings provide guidance for developing human capital profiles that include general as well as specific types of training to enhance marketability following a job loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…Social capital, on the other hand, encompasses the “knowing‐whom” competencies and is concerned with both formal and informal networks that provide career related information which affects reemployment prospects (McArdle et al, ). In general, individuals with high levels of human and social capital were more successful in gaining reemployment after job loss (Gowan & Lepak, ). Although the importance of human and social capital has been thoroughly examined, systematic attention on how psychological capital affects the reemployment process is lacking.…”
mentioning
confidence: 99%
“…Social capital, on the other hand, encompasses the “knowing‐whom” competencies and is concerned with both formal and informal networks that provide career related information which affects reemployment prospects (McArdle et al, ). In general, individuals with high levels of human and social capital were more successful in gaining reemployment after job loss (Gowan & Lepak, ). Although the importance of human and social capital has been thoroughly examined, systematic attention on how psychological capital affects the reemployment process is lacking.…”
mentioning
confidence: 99%
“…Indeed, human resource systems influence two decisions salient for stars: pay and firm strategy by clarifying what economists call decision rights, or internal organizational agreements about who has the power to make decisions about specific aspects of the firm's operation (e.g., Jensen and Meckling, 1995). Of particular interest are decisions about compensation practices and how much of the value the star creates and captures (i.e., value-appropriation decision rights) and decisions about the strategies the firm pursues and how those strategies are implemented (i.e., rights of control) (Delery, Gupta, and Shaw 1997;Gowan and Lepak 2007;Kang, Morris, and Snell 2007;Lepak and Snell 1999;Huselid, 1995;MacDuffie 1995;Rousseau 1995;Tsui, Pearce, Porter Tripoli 1995). Similarly, RBT and TCE both indicate that the firm should retain star employees (to provide a social context for the value creation, or to enable managerial fiat and value appropriation, respectively).…”
Section: Star Employees and Dynamic Value Capturementioning
confidence: 99%
“…Furthermore, these studies showed that some specific HRM practices were strategically designed to be different for various employee groups based on their HC. Such HRM practices included the retention strategy (Gardner, 2005), compensation (Gowan & Lepak, 2007;Hong & Honig, 2016;McDonnell et al, 2016), career management (De Vos & Urtasun & N uñez, 2012), pay and performance management systems (Ferner & Almond, 2013), organizational socialization tactics (Benzinger, 2016), skill development (Okay-Somerville & Scholarios, 2019), and training (Meli an-Gonz alez & Verano- Tacoronte, 2004;Vyas & Zhu, 2017).…”
Section: Empirical Validationsmentioning
confidence: 99%